PENGENALAN TUMBUHAN LOKAL UNTUK KOSMETIK KEPADA GEN Z: EDUKASI FORMULASI SEDIAAN MOISTURIZER EKSTRAK DAUN BENALU DUKU SEBAGAI AGENT PROTECTOR SKIN BARRIER DI SMKS GALANG INSAN MANDIRI - Syafitri, Anggun; harnis, zola efa; amar, ageng azhar; tamba, agnes clara; Mardatillah, Hazimah Fithryyah (Jurnal Pengabdian Masyarakat Putri Hijau, 2025)
This activity aims to introduce local plants, especially duku mistletoe leaves (Dendrophthoe pentandra), as a natural ingredient in the formulation of cosmetic preparations, especially moisturizers, to generation Z. This activity was carried out at Galang Insan Mandiri Vocational School and aims to provide education about the benefits of duku mistletoe leaves as a skin barrier protective agent. With increasing awareness of the importance of sustainability and the use of natural ingredients, it is hoped that this education can encourage the younger generation to prefer local products that are not only safe for skin health but also support the local economy. The outreach methods used include seminars and interactive discussions, which are expected to increase students' knowledge about natural ingredient-based skin care. It is hoped that the results of this activity can make a positive contribution to the development of the natural ingredient-based cosmetics industry in Indonesia.